Effect of Surface Modification on Nanoparticle Mixture-to-oil Migration Properties of Nanorefrigerant-oil Mixture - Chang Zheng; Lin Lingnan; Ding Guoliang; Peng Hao (Zhileng xuebao)
Nanoparticles are likely to aggregate in the oil-rich layer during the boiling of nanorefrigerant–oil mixtures, leading to a low mixture-to-oil migration ratio and making it difficult for nanoparticles to circulate with working fluid in a refrigeration system. Surface modification is a promising approach to raising the mixture-to-oil migration ratio, as it offers the ability to suppress aggregation. In this study, the mixture-to-oil migration ratio of nanoparticles modified by different alkyl chain lengths and grafting mechanisms was measured based on the absorbance method and the effects of the alkyl chain length of the modifier and the grafting mechanisms on the migration characteristics were examined. TiO2 nanoparticles, R141b refrigerant, and NM56 oil were used to prepare the nanorefrigerant–oil mixture. The surface modifiers included C1TMS, C3TMS, C8TMS, C16TMS, and CTAB. The experimental results show that the mixture-to-oil migration ratio increases after the application of these modifiers. The C16TMS exhibits the best enhancement (increasing the migration ratio by 131.2%). It is also found that the mixture-to-oil migration ratio increases by 5.48%–20.11% as the alkyl chain length increases from 1 to 16. The modified nanoparticles grafted by covalent bonds exhibit better migration performance than those that rely on electronic attraction.